2016
DOI: 10.1186/s12985-016-0658-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity of dengue virus type 2 in brain and thymus of infected interferon receptor ko mice: implications for dengue virulence

Abstract: BackgroundWe previously reported that a clinical isolate of dengue virus (DENV) is capable of causing acute-phase systemic infection in mice harboring knockouts of the genes encoding type-I and -II interferon IFN receptors (IFN-α/β/γR KO mice); in contrast, other virulent DENV isolates exhibited slow disease progression in this mice, yielding lethal infection around 20 days post-infection (p.i.). In the present study, we sought to clarify the dynamics of slow disease progression by examining disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…DENV tropism-based studies in mice models revealed varying results as in human studies. DENV antigens were detected in the skin, liver, spleen, lymph nodes, kidney, bone marrow, lung, thymus, brain, stomach, and intestine of the infected mice models as studied by various researchers and the results were similar to DENV-infected human autopsy studies [16,18,19,90,111,112,119]. The same primary targets were identified by other authors when they studied DENV infection in the humanized mouse model and concluded the presence and replication of DENV2 in blood along with its presence in monocytes, macrophages, T and B cells in spleen and in bone marrow [118].…”
Section: Tropism In Mousesupporting
confidence: 60%
See 1 more Smart Citation
“…DENV tropism-based studies in mice models revealed varying results as in human studies. DENV antigens were detected in the skin, liver, spleen, lymph nodes, kidney, bone marrow, lung, thymus, brain, stomach, and intestine of the infected mice models as studied by various researchers and the results were similar to DENV-infected human autopsy studies [16,18,19,90,111,112,119]. The same primary targets were identified by other authors when they studied DENV infection in the humanized mouse model and concluded the presence and replication of DENV2 in blood along with its presence in monocytes, macrophages, T and B cells in spleen and in bone marrow [118].…”
Section: Tropism In Mousesupporting
confidence: 60%
“…As the IFN response in mice helps in the clearance of DENV, researchers have tried to develop an immune-compromised mice model deficient in IFN-α /β and -γ receptors (AG129) or deficient in IFN-α /β receptor only (A129) in the 129/Sv background to study DENV pathogenesis [16,18,19,[110][111][112]. They are highly susceptible to DENV infection, resulting in high levels of viremia and vascular leakage [113,114].…”
Section: Tropism In Mousementioning
confidence: 99%
“…In vivo testing of the efficacy of Abs is carried out in mouse models, but only a limited number of DENV strains cause death in these models at an early time point (< 12 days) with human-like symptoms, such as increased vascular permeability 7 , 9 , 10 . Although high doses of some other DENV strains cause lethal infections in IFN-α/βR–γR dKO mice, most of these deaths are caused by the spread of virus into the brain at a late stage after clearance of virus from other organs 10 , 24 , which does not resemble the pathology of severe dengue fever in humans. Notably, our chimeric virus, DV2ChimV caused death at an early time point, and induced vascular permeability, especially in the liver and intestine at the moribund stage (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate signs of DENV in the CNS causing a panencephalitis at time of death and at biopsy 33 months antemortem. In murine models of DENV infection with enriched viral presence in the CNS, both the inoculum and viruses harboring mutants in the envelope gene were detected in the brain, 23 suggesting that envelope mutations are not needed to establish CNS infection. 20,21 Prior to 2008, DENV-2 and -3 were predominant, with no DENV-1 genotype V in circulation; in 2009 DENV-2 and -3 were again the predominant circulating strains.…”
Section: Discussionmentioning
confidence: 99%
“…As the vast majority of immune responses are directed at the viral envelope, the emergence of quasispecies of DENV‐1 enriched in envelope mutations likely reflects viral selection due to the rigorous ongoing immune pressures against DENV observed in the CNS of this patient. In murine models of DENV infection with enriched viral presence in the CNS, both the inoculum and viruses harboring mutants in the envelope gene were detected in the brain, suggesting that envelope mutations are not needed to establish CNS infection. However, it may be that the quasispecies detected in this patient escaped immune pressure and contributed to the chronic infection observed here.…”
Section: Discussionmentioning
confidence: 99%